Teaching English in higher establishments of Romania. - Гладкоскок, Леся Григорівна (Наукові праці Кам’янець-Подільського національного університету імені Івана Огієнка, 2020)
The present article discusses the issue of teaching English in Romanian higher educational institutions and its topicality nowadays. English is conquering new and new horizons of technological and scientific development. It is the language of new literature and entertainment, new thinking in economics and management. Also, it gives green light to new technologies and, consequently, there appear new ways of speaking and writing, new grammatical forms and vocabulary. English as a foreign language is taught in most countries of the world, Romania as well. Here the language is taught at all levels of the system and it is a means of Romanian undergraduate students’ development, as it is the world-wide language of trade, diplomacy, business, technology, music and all the other spheres of people’s life. As it was stated before, English has become the main medium of communication, and no wonder that a great number of academic curricula include English. As students of other countries, Romanian undergraduate students were also taught English since their early childhood via pop culture, movies, music and the Internet and all that facilitated students’ interest in English. English as a foreign language takes a very important place in Romanian education system, it’s one of the main subjects in students’ curricula and it explains the fact why the authorities try to draw Romanian education nearer to the European standards. As the globalization influences educational sphere, a lot of Romanian higher institutions have to look for new strategies for multicultural educational process, where the role of the English language is invaluable. A lifelong experience of teaching English both to English and non-English majors, some of them being Romanians, self-study, attending in class lessons, courses of the Romanian language, systematic listening to both English and Romanian speech, work with the dictionaries, watching films and attending festivals prompted the writing of this article with the aim of thorough study of Romanian experience of teaching English at higher institutions. Thorough explanations of the structure, types and cycles of the Higher Education System in Romania, admission requirements, curricula, teaching methods, student assessment, certification, employability, lifelong learning programs prove to be helpful for better understanding of how the system works. Alongside the analysis of different reasons of Romanian success story in this respect some phenomena in two languages – English and Romanian – are being elucidated. The similiarities found can be helpful in teaching/ learning activity.
Keywords: globalization; EFL (English as a foreign language); borrowings; terms; lexical units; bilingual dictionary.